Iron deficiency in patients with coronary artery disease - D. R. Khastieva; N. R. Khasanov (Российский кардиологический журнал)
A number of studies have demonstrated the negative impact of iron deficiency (ID) on the prognosis and course of heart failure. The prevalence of patients with coronary artery disease (CAD) in these studies was 39,4-65%, while the proportion of patients who had myocardial infarction reached 60%. The effect of ID on CAD course requires further study. The aim of this review was to analyze the available data on the effect of ID on heart function, quality of life, and prognosis in patients with CAD. This literature review analyzed 359 publications and systematized information on ID prevalence in patients with CAD, pathophysiological effects of ID on the function and structure of cardiomyocytes, the impact of ID on the course, prognosis, and quality of life in patients with CAD. The influence of ID and its correction on cardiomyocytes and left ventricular systolic function were studied.